Mouse papillomavirus infection persists in mucosal tissues of an immunocompetent mouse strain and progresses to cancer. Issue 1 (December 2017) - Cladel, Nancy; Budgeon, Lynn; Balogh, Karla; Cooper, Timothy; Brendle, Sarah; Christensen, Neil; Schell, Todd; Hu, Jiafen
Abstract Mouse papillomavirus has shown broad tissue tropism in nude mice. Previous studies have testedcutaneous infections in different immunocompromised and immunocompetent mouse strains. In the current study, we examinedmucosal infection in several immunocompetent and immunocompromised mouse strains. Viral DNA was monitored periodically by Q-PCR of lavage samples. Immunohistochemistry andin situ hybridization were used to determine viral capsid protein and viral DNA respectively. All athymic nude mouse strains showed active infections at both cutaneous and mucosal sites. Interestingly, NOD/SCID mice, which have a deficiency in T, B, and NK cells, showed minimal disease at cutaneous sites but developed persistent infection at the mucosal sites including those of the anogenital region and the oral cavity. Three strains ofimmunocompetent mice supported mucosal infections. Infections of the lower genital tract in heterozygous (immunocompetent) mice of the NU/J strain progressed to high grade dysplasia and to carcinomain situ . Anti-MmuPV1 neutralizing antibodies were detected in the sera of all immunocompetent animals. Our findings demonstrate that the mucosae may be the preferred sites for this virus in mice. The mouse model is expected to be a valuable model for the study of mucosal papillomavirus disease, progression, and host immune control.